Chemical composition and antibacterial activity of commercial copaiba (Copaifera spp.) oils against bacterial pathogens isolated from postoperative mammoplasty surgery (Research, Society and Development, 2020)
Plastic surgeries are considered clean or potentially contaminated procedures. The incidence of infection in reduction mammoplasty is 1.1 to 22% and the main etiological agents are bacteria found on the skin and mucous membranes such as Staphylococcus aureus. Due to the increase in bacterial resistance with the widespread use of antibiotics, identify natural compounds with antibacterial action on postoperative surgery wounds are fundamental. Thus, the objective of this research was the identification of compounds and assessment of the antibacterial action of Copaifera spp. (copaiba) oil against standard strains and bacterial pathogens isolated from postoperative mammoplasty surgery. For this, four commercial copaiba oils (1, 2, 3 and 4) were submitted to a gas chromatography/mass spectrometry analysis. The in-vitro antimicrobial activity and the minimum inhibitory concentration (MIC) of oils on standard strains and clinical samples, as well as the disk antibiotics sensitivity and the synergistic effect of the oils and antibiotics, were assessed. A total of 72 compounds were identified, accounting for ~99% of the volatile constituents in the oils. Sesquiterpenes comprised 67.24– 90.11% of the components, with β-caryophyllene being the most common. Oils 1 and 2 were the most active on the S. aureus strain, with MIC similarto Oil 3, while Oil 4presented no activity. The same pattern was observed in the clinical samples. In addition, Oil 2 presented synergism when associated with amoxicillin. The synergistic effects of Copaiba oils may represent a source of therapeutic compounds against bacterial infections in surgical wound.